The Handbook of Culture and Psychology 2019
DOI: 10.1093/oso/9780190679743.003.0014
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Psychology and Culture

Abstract: More than a century of research on culture and psychopathology has shown that culture exerts a major influence on the identification, labeling, indigenous meaning, course, and outcome of maladaptive behaviors. The major goal of this chapter is to appraise the current state of knowledge of the relationship between culture and psychopathology. More specifically, this chapter aims to identify the contribution of different conceptual and methodological approaches to investigating the relationship between culture a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In today’s world, social interactions can occur with anyone from any social or cultural background and at any place for various purposes. For example, rapport is critically important in therapeutic settings, and understanding perceptions of rapport across cultures may have implications for therapeutic work across cultures, as it has its own share of culturally unique aspects (Tanaka-Matsumi, 2019). In the investigative interviewing world, the current findings may provide a relatively simpler roadmap to establishing and maintaining rapport, much along the lines that Tickle-Degnan and Rosenthal (1990) posited years ago that positivity can play an important role, especially in the beginning of an interaction, at least involving interviews with naïve individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In today’s world, social interactions can occur with anyone from any social or cultural background and at any place for various purposes. For example, rapport is critically important in therapeutic settings, and understanding perceptions of rapport across cultures may have implications for therapeutic work across cultures, as it has its own share of culturally unique aspects (Tanaka-Matsumi, 2019). In the investigative interviewing world, the current findings may provide a relatively simpler roadmap to establishing and maintaining rapport, much along the lines that Tickle-Degnan and Rosenthal (1990) posited years ago that positivity can play an important role, especially in the beginning of an interaction, at least involving interviews with naïve individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence found that depression and mental states among Arab adolescents are constructed and expressed differently than among adolescents in other cultures [30]. Culture may play a role in differences in frequency of disorders in different groups [31]. Also, socio-cultural factors may also play a part in how distress is expressed [32].…”
Section: Discussionmentioning
confidence: 99%
“…The indigenous approach stresses things that are particularistic or unique in a given culture, otherwise known as emics (Ægisdóttir et al, 2008). The indigenous approach is relativistic as it studies in depth a local culture and the meaning of constructs without any theoretical imposition on the constructs (Tanaka-Matsumi, 2001). Thus, as observed by Jenkins (2009) in the African context, time is perceived as something that flows backwards.…”
Section: Factors That Hindered Access To Research Sites and Participantsmentioning
confidence: 99%